The Binding Affinity and Molecular Basis of the Structure-Binding Relationship between Urinary Tamm-Horsfall Glycoprotein and Tumor Necrosis Factor-α - Chia-Li Yu; Chang-Youh Tsai; Tsai-Hung Wu; Sue-Cien Siao; Yu-Hsuan Chen; Ko-Jen Li; Cheng-Han Wu (Molecules, 2012)
In a previous study we noted significant THP binding to TNF-α, but did not explore the molecular basis of the structure-binding relationship. In this study, we used lectin-binding ELISA to assess the carbohydrate compositions of THP, BSA, IgG, TNF-α, and IFN-g. We identified β(1,4)-N-acetylglucosamine oligomers (GlcNAc) and GlcNAc/branched mannose in BSA, IgG, TNF-α, and THP, but not in IFN-g. These carbohydrate moieties mediated binding with THP. Small amounts of Siaα(2,3)Gal/ GalNAc, Sia(2,6)Gal/GalNAc, and mannose residues were also present in THP and TNF-α. Binding affinity (Kd) between THP and TNF-α by Scatchard plot analysis was 1.4–1.7 × 10−6 M, lower than antigen-antibody or ligand-receptor binding affinities. To elucidate the structure-binding relationship of THP-TNF-α, THP was digested with neuraminidase, β-galactosidase, O-sialoglycoprotein endopeptidase, carboxypeptidase Y, or proteinase K. β-galactosidase increased binding capacity of THP for TNF-α. Monosaccharide inhibition suggested that α-methyl-D-mannoside, GlcNAc, and GalNAc, but not sialic acid, suppress THP-TNF-α binding as detected by ELISA. We conclude that sugar-lectin and sugar-protein interactions between cognate sites in THP and TNF-α mediate their binding.